1988
DOI: 10.1007/bf02560100
|View full text |Cite
|
Sign up to set email alerts
|

Emergency colectomy for cytomegalovirus ileocolitis in patients with the acquired immune deficiency syndrome

Abstract: The charts of all patients with the acquired immune deficiency syndrome (AIDS) who underwent emergency intra-abdominal surgery between January 1981 and July 1987 were reviewed. Eleven AIDS patients underwent 13 emergency laparotomies. Seven of these patients (64 percent) had cytomegalovirus (CMV) ileocolitis as the pathologic process requiring emergent surgical intervention. Four patients had hemorrhagic CMV proctocolitis and three had perforations of CMV ulcers of the ileum or rectosigmoid. The operations per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0
1

Year Published

1989
1989
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(25 citation statements)
references
References 21 publications
2
22
0
1
Order By: Relevance
“…Postoperative prognosis, however, was very poor, since we found a 1-month postoperative mortality of 60%. These results are in agreement with those of Wexner et al (5) and Wilson et al (25), who reported 1-month mortalities of 71% and 46%, respectively, in their series of patients undergoing emergency laparotomy for abdominal pain. However, it is possible that earlier surgical intervention, before perforation and peritonitis intervene, and the use of zidovudine or ddI may ameliorate the postoperative prognosis of these patients, as suggested by recent experience (7).…”
Section: Discussionsupporting
confidence: 95%
See 3 more Smart Citations
“…Postoperative prognosis, however, was very poor, since we found a 1-month postoperative mortality of 60%. These results are in agreement with those of Wexner et al (5) and Wilson et al (25), who reported 1-month mortalities of 71% and 46%, respectively, in their series of patients undergoing emergency laparotomy for abdominal pain. However, it is possible that earlier surgical intervention, before perforation and peritonitis intervene, and the use of zidovudine or ddI may ameliorate the postoperative prognosis of these patients, as suggested by recent experience (7).…”
Section: Discussionsupporting
confidence: 95%
“…With regard to the causes of abdominal pain, it is not surprising that HIV-related disorders clearly predominated over non-AIDS-related diseases in this population; this concurs with the results of previous experiences, all showing that most of the disorders responsible for pain are strictly associated with the immunocompromised state and are often infective (2)(3)(4)(5)(6)(7)(8)(9). The commonest single cause of severe pain in the present series was GI NHL; the GI tumor always occurred in patients who also had lymphoma outside the gastrointestinal tract.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In order to establish whether HIV and AIDS patients are subject to an increased risk of wound complications and poor healing, a wound other than that of the anorectal canal requires investigation. Several authors have described a high rate of wound complications and problems with wound healing following laparotomy [16, 17, 18, 19, 20]. These observations in various reports require clarification and the prognostic factors, both clinical and immunological, which may lead to poor healing need to be defined.…”
Section: Introductionmentioning
confidence: 99%